Intracellular DNA Damage by Lysine-Acetylene Conjugates - Wang-Yong Yang; Qiang Cao; Catherine Callahan; Catalina Galvis; Qing-Xiang Sang; Igor V. Alabugin (Journal of Nucleic Acids)
Previously, we reported the design and properties of alkyne C-lysine conjugates, a powerful and tunable family of DNA cleaving reagents. We also reported that, upon photoactivation, these molecules are capable of inducing cancer cells death. To prove that the cell death stems from DNA cleavage by the conjugates, we investigated intracellular DNA damage induced by these molecules in LNCap cancer cells using single cell gel electrophoresis (SCGE) assays. The observation of highly efficient DNA damage confirmed that lysine acetylene conjugate is capable of cleaving the densely compacted intracellular DNA. This result provides a key mechanistic link between efficient DNA cleavage and cytotoxicity towards cancer cells for this family of light-activated anticancer agents.